Osteogenesis and aging: lessons from mesenchymal stem cells - Infante, Arantza (Stem Cell Res Ther, 2018)
Aging is a high risk factor for the development of osteoporosis, a multifactorial age-related progressive disease characterized by reduced bone mass and increased risk of fractures. At the cellular level, the mesenchymal stem cell pool in the bone marrow niche shows a biased differentiation into adipogenesis at the cost of osteogenesis. This differentiation shift leads to decreased bone formation, contributing to the etiology of osteoporosis. This review will focus on the most recent/relevant molecular findings driving this functional impairment of mesenchymal stem cells in the aging process.